Comprehensive Geriatric Assessment in Oncology: Best Practices in Caring for Older Patients - Overcash, Janine (J Adv Pract Oncol, 2018)
CASE STUDY Michele Green received the results of her breast cancer biopsy last week. Before surgery for infiltrating ductal carcinoma to her left breast, Michele was advised to meet with the members of the Senior Adult Oncology Program (SAOP) at the cancer center. A phone call from a nurse explained that the 2-hour visit with the SAOP would include meetings with many providers, such as a physical therapist, a social worker, a dietitian, a pharmacist, a nurse practitioner, and an oncologist to undergo a comprehensive geriatric assessment. Driving to her appointment, Michele wondered why her visit would take so long and why she had to see so many people. At 81 years old, Michele maintains her physical fitness and has never really been sick. She continues to work each week at the university and engages in an active social life. What could a team possibly find? Walking past the many examination rooms, Michele began to feel despair that she was now a "cancer patient."